The Lived Experience of Losing a Sibling through Murder. - Pretorius, Gertie; Halstead-Cleak, Julia; Morgan, Brandon (Indo-Pacific Journal of Phenomenology, 2010)
This study explores the grief experiences of young adults in the aftermath of the murder of a sibling. Three young adults were recruited to participate in interviews in which they described their lived experience of loss. Data collection and the subsequent analyses were guided by a phenomenological research design and resulted in the identification of seven major themes, namely (1) shock and disbelief, (2) recollection, guilt and self-blame, (3) rupture and fragmentation, (4) support, (5) justice and revenge, (6) reformulation, and (7) resilience, healing and growth. These themes are discussed with reference to the findings of other documented studies, and the implications for practitioners working with bereaved siblings of murder victims pointed to.